Baseline serum cholestanol as predictor of recurrent coronary events in subgroup of Scandinavian simvastatin survival study - Miettinen, Tatu A (British Medical Journal, 1998)
Objectives: To investigate whether baseline serum cholestanol:cholesterol ratio, which is negatively related to cholesterol synthesis, could predict reduction of coronary events in the Scandinavian simvastatin survival study. Design: Follow up of patients with coronary heart disease in whom baseline ratios were related to major coronary events. Setting: Four universities in Finland. Subjects: A subgroup of 868 patients with coronary heart disease selected from the Scandinavian simvastatin survival study. Intervention: Treatment with simvastatin or placebo. Main outcome measures: Serum concentrations of low density lipoprotein and high density lipoprotein cholesterol, total triglyceride concentration, and cholesterol:cholestanol ratio. Major coronary events. Results: With increasing baseline quarter of cholestanol distribution the reduction in relative risk increased gradually from 0.623 (95% confidence interval 0.395 to 0.982) to 1.166 (0.791 to 1.72). The risk of recurrence of major coronary events increased 2.2-fold (P<0.01) by multiple logistic regression analysis between the lowest and highest quarter of cholestanol. The ratio of cholestanol was related inversely to the body mass index and directly to high density lipoprotein cholesterol and triglyceride concentrations but their quarters of distribution were not related to risk reduction. Conclusions: Measurement of serum cholestanol concentration revealed a subgroup of patients with coronary heart disease in whom coronary events were not reduced by simvastatin treatment. Thus, patients with high baseline synthesis of cholesterol seem to be responders whereas those with low synthesis of cholesterol are non-responders.